Power play: The dynamics of power and interpersonal communication in higher education as reflected in David Mamet’s Oleanna - Chiaramonte, Peter (Canadian Journal of Higher Education, 2014)
David Mamet’s play Oleanna may be infamous for reasons that do not do justice to the play’s real accomplishments. One reason for the controversy is the author’s apparent focus on sexual harassment. The play is not about sexual harassment. It is about power. And in particular the power of language to shape relationships within social environments such as universities. First published and performed in 1992 - at a time when many were outraged by the Clarence Thomas - Anita Hill debate - the playwright himself was compelled to deny his play was about sexual aggravation. Mamet’s Oleanna serves to instruct us about the power dynamics within one of our most vital institutions. The aim of this article is to take a dedicated look at this dramatic spectacle to see if we cannot uncover something about leadership and the mechanics of power and communication in higher education that is intellectually riveting, as well as socially constructive.